Tumor Associated Macrophages: Origin, Recruitment, Phenotypic Diversity, and Targeting - Hourani, Tetiana; Holden, James A.; Li, Wenyi; Lenzo, Jason C.; Hadjigol, Sara; O’Brien-Simpson, Neil M. (Frontiers in Oncology, 2021)
The tumor microenvironment (TME) is known to have a strong influence on tumorigenesis, with various components being involved in tumor suppression and tumor growth. A protumorigenic TME is characterized by an increased infiltration of tumor associated macrophages (TAMs), where their presence is strongly associated with tumor progression, therapy resistance, and poor survival rates. This association between the increased TAMs and poor therapeutic outcomes are stemming an increasing interest in investigating TAMs as a potential therapeutic target in cancer treatment. Prominent mechanisms in targeting TAMs include: blocking recruitment, stimulating repolarization, and depletion methods. For enhancing targeting specificity multiple nanomaterials are currently being explored for the precise delivery of chemotherapeutic cargo, including the conjugation with TAM-targeting peptides. In this paper, we provide a focused literature review of macrophage biology in relation to their role in tumorigenesis. First, we discuss the origin, recruitment mechanisms, and phenotypic diversity of TAMs based on recent investigations in the literature. Then the paper provides a detailed review on the current methods of targeting TAMs, including the use of nanomaterials as novel cancer therapeutics.